Designing a Warm-Up Protocol for Elite Bob-Skeleton Athletes - Cook, C.; Holdcroft, D.; Drawer, S.; Kilduff, L. P. (International Journal of Sports Physiology and Performance, 2013)
Purpose: To investigate how different warm-ups influenced subsequent sled-pull sprint performance in Olympic-level bob-skeleton athletes as part of their preparation for the 2010 Winter Olympics. Methods: Three female and 3 male athletes performed 5 different randomized warm-ups of differing intensities, durations, and timing relative to subsequent testing, each 2 days apart, all repeated twice. After warm-ups, testing on a sledpull sprint over 20 m, 3 repeats 3 min apart, took place. Results: Performance testing showed improvement (P < .001, ES > 1.2) with both increasing intensity of warm-up and closeness of completion to testing, with 20-m sled sprinting being 0.1-0.25 s faster in higher-intensity protocols performed near testing In addition, supplementing the warm-ups by wearing of a light survival coat resulted in further performance improvement (P = .000, ES 1.8). Conclusions: Changing timing and intensity of warm-up and using an ancillary passive heat-retention device improved sprint performance in Olympic-level bob-skeleton athletes. Subsequent adoption of these on the competitive circuit was associated with a seasonal improvement in push times and was ultimately implemented in the 2010 Winter Olympics.